The Use of Technology as a Health Promotion Strategy on Stunting Knowledge in Nursing Students Pasca The Covid-19 Pandemic - Hairuddin K. Hairuddin K.; Dian Meiliani Yulis; Serli Serli (Jurnal Penelitian Pendidikan IPA, 2023)
According to WHO, the primary causes of stunting in children under five years old include infections, insufficient infant and child feeding practises, and poor maternal health and nutrition. This study aimed to investigate the use of Technology as a health promotion strategy for stunting knowledge in nursing students during the COVID-19 pandemic. This study used an analytic study using a quasi-experimental study. The sampling technique used purposive sampling. The sample in this study was 22 respondents in health university students, with a total population of 45 respondents. The findings revealed that the use of animation-based technology in health promotion can help nursing science students at the Faculty of Nursing and Midwifery of Megarezky University learn more about stunting, including how to provide children with enough nutrition and how to parent stunted children. Animation-based Technology makes information easier to understand and allows for repetition; it has an impact on nursing students' understanding of stunting and how to promote health effectively.